Gamma radiation treatment to ensure microbial safety of ready to bake (RTB) vegetable toppings/ fillers and retain their nutritional qualities during cold storage. (November 2020) - Bandyopadhyay, Nilantana C.; More, Varsha; Tripathi, Jyoti; Gautam, Satyendra
Abstract: Limited shelf life due to processing associated microbial contamination is one of the major challenging issues with minimally processed 'Ready to Bake' (RTB) vegetable products leading to huge post-processing losses. In the current study, three minimally processed vegetables, i.e. tomato, bell pepper and white onion, which are widely used in fast food industries (FFI), such as pizza and burger as well as in households; were studied for their post-processing microbiological profile; and to assess the effect of gamma radiation treatment (0.5–5 kGy) to maintain hygiene during extended storage at low temperature. Prior to radiation treatment, the minimally processed vegetables were packed in low density polyethylene bags (thickness: 50 μm) which is suitable for such agri-produce and compatible to gamma radiation treatment (USA, FDA). Besides, vacuum packaging in multilayered LDPE bags was optimized for shredded onion. Except tomato, which did not contain any detectable presumptive coliform or yeast and mold on day 0, the other two cut vegetables were found to have higher load of microbes, i.e., more than 4.0 log CFUg −1 of total aerobic plate count, 3.0 log CFUg −1 of each of yeast and mold counts (YMC) and presumptive coliform (PC) counts. In the radiation treated (2 kGy) vegetables, no PC was detected; even after 20 days of storage; whereas, in the untreated bell pepper, tomato and onion samples PC counts were found to be 4.3 ± 0.1, 3.7 ± 0.2 and 1.7 ± 0.3 log CFUg −1 respectively on day 20 of storage. The data indicated that, the total aerobic plate counts in the 2 kGy irradiated samples were below the permissible limit as per the Food Safety and Standards Authority of India (FSSAI) guidelines. Organoleptic attributes ('colour', 'texture', 'flavour', 'taste' and 'overall acceptability') of the radiation treated products were found to be well retained even on 20 days of storage. The nutritional adequacy of these products in terms of total energy, fat, protein, carbohydrate, minerals and vitamin content was found to be well retained till the end of the 20 days' storage period. Findings of the study thus establish the efficacy of gamma radiation treatment in ensuring the safety and quality of minimally processed vegetables for their use in FFI as well as domestic kitchens. Highlights: Pre-cut bell pepper, onion and tomato are extremely perishable fast food ingredients. Gamma irradiation extended shelf life of these minimally processed vegetables. Pre-packed radiation treated (2 kGy) products lasted for 20 days at 4–6 °C. The treatment ensured microbiological safety during storage. Organoleptic attributes and nutritional parameters were also well retained.